PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA DI KELAS V SDN 101821 PANCUR BATU - Sitohang, Juita; Patri Janson Silaban; Eka Kartika Silalahi; Regina Sipayung; Darinda Sofia Tanjung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Think Pair Share Cooperative learning model on student learning outcomes in Mathematics learning in grade V of SD Negeri 101821 Pancur Batu in the 2024/2025 Academic Year. This study uses a quantitative method with a pretest-posttest experimental design in one group, involving 24 students as a sample. Data collection was carried out through learning outcome tests and student participation questionnaires that have been tested for validity and reliability. The pretest results showed an average value of student learning outcomes of 60.45 with a sufficient category, while the posttest results increased to 77.20 with a high category. The Pearson correlation test produced a coefficient of 0.949 with a significance of 0.000, which indicates a strong positive relationship between the application of the Think Pair Share Cooperative learning model and student learning outcomes. Furthermore, the results of the hypothesis test using the t-test obtained a calculated t value ≥ t table, namely 2.575 ≥ 1.711, which means there is a significant influence between the use of the Think Pair Share Cooperative learning model on student learning outcomes. Thus, the research hypothesis states that there is a significant influence of the Think Pair Share Cooperative learning model on student learning outcomes.